2012
DOI: 10.1073/pnas.1212665109
|View full text |Cite
|
Sign up to set email alerts
|

Membrane physical properties influence transmembrane helix formation

Abstract: The pHLIP peptide has three states: (I) soluble in aqueous buffer, (II) bound to the bilayer surface at neutral pH, and (III) inserted as a transmembrane (TM) helix at acidic pH. The membrane insertion of pHLIP at low pH can be used to target the acidic tissues characteristic of different diseases, such as cancer. We find that the α-helix content of state II depends on lipid acyl chain length but not cholesterol, suggesting the helicity of the bound state may be controlled by the bilayer elastic bending modulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 49 publications
6
74
2
Order By: Relevance
“…This concept of using simple hydrophobicity calculations of the putative spanning domain to correctly predict the change in direction of the insertion pKa is something we have also done in other recent work 19 using membranes of different acyl chain length. In this other work, we found that MPEx results were also good predictors of pHLIP’s insertion pKa in lipids of short to intermediate core thicknesses, leaving some hope that the semblance of an average may yet have practical use in our system.…”
Section: Discussionmentioning
confidence: 89%
“…This concept of using simple hydrophobicity calculations of the putative spanning domain to correctly predict the change in direction of the insertion pKa is something we have also done in other recent work 19 using membranes of different acyl chain length. In this other work, we found that MPEx results were also good predictors of pHLIP’s insertion pKa in lipids of short to intermediate core thicknesses, leaving some hope that the semblance of an average may yet have practical use in our system.…”
Section: Discussionmentioning
confidence: 89%
“…The proline-20 to glycine variant exhibited α-helical structure in both State II and State III, leading to promiscuous insertion activity at a broad pH range, with a far lower apparent cooperativity of insertion than WT pHLIP (35). Proline, known commonly to destabilize helices due to its conformational constraints, is likely to limit the α-helicity of pHLIP peptides in States I and II, maintaining a high energy barrier to membrane insertion until protonation of the transmembrane acidic residues promotes helix formation during the State II to State III transition.…”
Section: Biochemical and Biophysical Characteristicsmentioning
confidence: 98%
“…While the longer acyl-chain liposomes exhibit an increased stiffness, cholesterol concentration has no effect on the bending modulus of monounsaturated membranes (71, 72). A likely conclusion, therefore, is that the elastic properties of the bilayer influence helix formation on the membrane surface (35). Cell experiments suggest that membrane fluidity is more determinant that membrane thickness in controlling pHLIP’s pK ins .…”
Section: Biochemical and Biophysical Characteristicsmentioning
confidence: 99%
“…3,4 Thus, these macromolecules are able to switch their conformations upon sensing environmental perturbations. There are a variety of such perturbations, such as interaction with another macromolecule, 1,5 interaction with a ligand, 6 solvent conditions 710 -(polarity and pH), physical environment 1115 (salt, pressure, temperature, and light), or post-translational modifications. 13,16 …”
mentioning
confidence: 99%